CONSTRUCTION CHALLENGE OF SUBMERGED FLOATING TUNNEL IN INDONESIA - ery budiman (Universitas Mulawarman, 2017)
Indonesia is an archipelagic country which consisting of many islands that require competitive crossing technology. Submerged floating tunnel (SFT) responds to this challenge and comes as a competitive crossing technology. SFT structure has superior advantages to conventional crossing technologies but it also has some disadvantages especially in keeping structural stability.Structural stability of SFT is mainly effected by site characterization and environmental disturbances. Geographical combination of water depth, crossing distance and overall dimension is one of the most important factors to decide the structu of Engimeeral design as well as environmental disturbances such as wave, current and earthquake.This paper presents descriptions of SFT structures, some of the SFT structure challenges and the opportunities of using SFT structures for various purposes in Indonesia.